The effects of COVID-19 in global warming through the application of data science - Rafia, Tasnim; Mahmood Hasan, Tanveer; Hassan, Raini (Universiti Kuala Lumpur Publishing, 2022)
Global warming and Covid-19, the two trending affairs, seem to be associated with each other. The research aims to look for climate change’s fundamental factors which are being affected by the Covid-19 pandemic, to prepare an overview with a prediction of future temperature conditions alongside, being inspired by Sustainable Development Goals 7 and 13. The entire study is going to be accomplished using Python and Machine Learning model (for data analysis & prediction), as well as Microsoft Excel (for creating a dashboard overview). The findings show that some factors emphatically getting influenced by this pandemic resulting in a positive impact on global warming. The study motivates research on other significant factors of climate change in the near future in order to find an effective way for climate change reduction.